The Influence of Using Kahoot on Students' Reading Comprehension at the Eighth Grade of SMP Negeri 17 Kota Serang - Syafita Maharani; Yudi Juniardi; Ledy Nurlely (English Department - Universitas Sultan Ageng Tirtayasa, 2022)
Reading is one of the language skills that should be mastered by students. In reading, we gain information and knowledge from written text. The objective of this research is to find out whether there is an influence of using Kahoot on students’ reading comprehension at the eighth grade of SMP Negeri 17 Kota Serang. The research methodology used was quasi-experimental. The researcher took two classes, one class as an experimental class and one class as a control class. To collect the data, the researcher used instruments consisting of multiple-choice questions of recount text which had been tried out before the treatment. The instrument consisted of pre-test and post-test. After collecting all the data, the researcher used t-test formula to test the hypothesis. From the calculation of the independent sample t-test, it resulted that tcount was 2.7940 and ttable was 2.0075. It means Ha is accepted because tcount > ttable. Therefore, there is an influence of using Kahoot on students’ reading comprehension at the eighth grade of SMP Negeri 17 Kota Serang in the academic year of 2021/2022.